Measuring Work-related Risk of Coronavirus Disease 2019 (COVID-19): Comparison of COVID-19 Incidence by Occupation and Industry—Wisconsin, September 2020 to May 2021. (19th August 2022) - Pray, Ian W; Grajewski, Barbara; Morris, Collin; Modji, Komi; DeJonge, Peter; McCoy, Katherine; Tomasallo, Carrie; DeSalvo, Traci; Westergaard, Ryan P; Meiman, Jonathan
Abstract: Background: Work-related exposures play an important role in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission, yet few studies have compared SARS-CoV-2 expsoure risk across occupations and industries. Methods: During September 2020 to May 2021, the Wisconsin Department of Health Services collected occupation and industry data as part of routine coronavirus disease 2019 (COVID-19) case investigations. Adults aged 18–64 years with confirmed or probable COVID-19 in Wisconsin were assigned standardized occupation and industry codes. Cumulative incidence rates were weighted for non-response and calculated using full-time equivalent (FTE) workforce denominators from the 2020 American Community Survey. Results: An estimated 11.6% of workers (347 013 of 2.98 million) in Wisconsin, ages 18–64 years, had COVID-19 from September 2020 to May 2021. The highest incidence by occupation (per 100 FTE) occurred among personal care and services workers (22.1), healthcare practitioners and support staff (20.7), and protective services workers (20.7). High-risk sub-groups included nursing assistants and personal care aides (28.8), childcare workers (25.8), food and beverage service workers (25.3), personal appearance workers (24.4), and law enforcement workers (24.1). By industry, incidence was highest in healthcare (18.6); the highest risk sub-sectors were nursing care facilities (30.5) and warehousing (28.5). Conclusions: This analysis represents one of the most complete examinations to date of COVID-19 incidence by occupation and industry. Our approach demonstrates the value of standardized occupational data collection by public health and may be a model for improved occupational surveillance elsewhere. Workers at higher risk of SARS-CoV-2 exposure may benefit from targeted workplace COVID-19 vaccination and mitigation efforts. Abstract : This study uses surveillance data to estimate the incidence of coronavirus disease 2019 (COVID-19) among workers in Wisconsin and compare risk across standardized occupation and industry groups. High incidence was found among workers in personal care and service occupations, healthcare, and law enforcement.